Suwerenność państwa - geneza i rozwój idei w prawie międzynarodowym: [State sovereignty - origins and development of the idea in international law] (Studia Prawnicze / The Legal Studies, 2002)
The concept of state sovereignty emerged at the turn of the Middle Ages and the Renaissance. The author of this article presents the concept of sovereignty, its origins and the history of its development in international law. It highlights the problem of formulating a definition of sovereignty and the fact that the term is understood in many ways, with such understanding caused, inter alia, by the very nature of legal language but also to the language of acts of international law. The author attempts to provide the readers with a clarification of the contemporary understanding of sovereignty by introducing the history of sovereignty itself and tracing the evolution of its interpretation.